Studi Kasus: Keperawatan Keluarga Dalam Pengendalian Kestabilan Kadar Gula Darah Pada Klien Diabetes Mellitus - Dwiharini Puspitaningsih; Kurniawati (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2021)
Success in treating diabetes mellitus patients requires a family role. One of the family roles of diabetes mellitus patients is controlling blood sugar levels of diabetes mellitus patients. This study aimed to provide diabetes mellitus family nursing care with an inability to controll blood sugar levels. The design used in this research was a case study. The study used 2 families. then diagnosed nursing intervention, implementation and evaluation. Data collection methods by interview, observation, and documentation using the family nursing care format. The results of the assessment of the two families showed the same results, namely were not knowing and were being unable to controlling blood sugar levels. After conducting three interventions which included counseling and assistance in is controlling blood sugar levels, which was carried out three times, the results were that the family understood and were able to controlling blood sugar levels of diabetes mellitus patients. Controlling blood sugar levels of diabetes mellitus patients at home is largely determined by the role of the family.